Plasma Lipid Mediators Associate With Clinical Outcome After Successful Endovascular Thrombectomy in Patients With Acute Ischemic Stroke - Hao, Jiheng; Feng, Yao; Xu, Xin; Li, Long; Yang, Kun; Dai, Gaolei; Gao, Weiwei; Zhang, Meng; Fan, Yaming; Yin, Tengkun; Wang, Jiyue; Yang, Bin; et al. (Frontiers in Immunology, 2022)
Background: Neuroinflammatory response contributes to early neurological deterioration (END) and unfavorable long-term functional outcome in patients with acute ischemic stroke (AIS) who recanalized successfully by endovascular thrombectomy (EVT), but there are no reliable biomarkers for their accurate prediction. Here, we sought to determine the temporal plasma profiles of the bioactive lipid mediators lipoxin A4 (LXA4), resolvin D1 (RvD1), and leukotriene B4 (LTB4) for their associations with clinical outcome. Methods: We quantified levels of LXA4, RvD1, and LTB4 in blood samples retrospectively and longitudinally collected from consecutive AIS patients who underwent complete angiographic recanalization by EVT at admission (pre-EVT) and 24 hrs post-EVT. The primary outcome was unfavorable long-term functional outcome, defined as a 90-day modified Rankin Scale score of 3-6. Secondary outcome was END, defined as an increase in National Institutes of Health Stroke Scale (NIHSS) score ≥4 points at 24 hrs post-EVT. Results: Eighty-one consecutive AIS patients and 20 healthy subjects were recruited for this study. Plasma levels of LXA4, RvD1, and LTB4 were significantly increased in post-EVT samples from AIS patients, as compared to those of healthy controls. END occurred in 17 (20.99%) patients, and 38 (46.91%) had unfavorable 90-day functional outcome. Multiple logistic regression analyses demonstrated that post-EVT levels of LXA4 (adjusted odd ratio [OR] 0.992, 95% confidence interval [CI] 0.987-0.998), ∆LXA4 (adjusted OR 0.995, 95% CI 0.991-0.999), LTB4 (adjusted OR 1.003, 95% CI 1.001-1.005), ∆LTB4 (adjusted OR 1.004, 95% CI 1.002-1.006), and post-EVT LXA4/LTB4 (adjusted OR 0.023, 95% CI 0.001-0.433) and RvD1/LTB4 (adjusted OR 0.196, 95% CI 0.057-0.682) ratios independently predicted END, and post-EVT LXA4 levels (adjusted OR 0.995, 95% CI 0.992-0.999), ∆LXA4 levels (adjusted OR 0.996, 95% CI 0.993-0.999), and post-EVT LXA4/LTB4 ratio (adjusted OR 0.285, 95% CI 0.096-0.845) independently predicted unfavorable 90-day functional outcome. These were validated using receiver operating characteristic curve analyses. Conclusions: Plasma lipid mediators measured 24 hrs post-EVT were independent predictors for early and long-term outcomes. Further studies are needed to determine their causal-effect relationship, and whether the imbalance between anti-inflammatory/pro-resolving and pro-inflammatory lipid mediators could be a potential adjunct therapeutic target.